PBT composite material, preparation method and application thereof
Patent Information
- Application Number
- CN202611353460.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]现行业普遍将POEg
GMA在溴锑阻燃玻纤增强PBT体系中作为增韧剂使用,在溴锑阻燃玻纤增强PBT中,溴系阻燃剂和PBT基体的相容性较好,低接枝率的POE-g-GMA即可实现增韧效果,但这一增韧技术无法直接应用于玻纤增强无卤阻燃PBT材料
[0025]本发明的有益效果主要体现在如下方面:
Smart Images

Figure SMS_26 
Figure SMS_27 
Figure SMS_28
Abstract
Description
Technical Field
[0001] This invention relates to the field of modified engineering plastics and polymer composite materials, and more specifically, to a PBT composite material, its preparation method, and its application. Background Technology
[0002] With the rapid upgrading of new energy vehicles, low-voltage electrical appliances, and the electronic information industry, polybutylene terephthalate (PBT) has become one of the core substrates for structural and functional components due to its excellent electrical insulation, chemical corrosion resistance, molding flowability, and dimensional stability. Reinforcing with 30% glass fiber by weight can significantly improve the material's tensile strength, flexural modulus, and heat resistance, making it the most widely used reinforcement specification in the industry. Meanwhile, due to environmental and safety requirements, halogen-free flame retardancy has become a mandatory standard for electronic and electrical components, leading to continued growth in market demand for phosphorus-nitrogen-based halogen-free flame-retardant PBT materials.
[0003] The industry generally uses PoE g GMA is used as a toughening agent in the bromine-antimony flame-retardant glass fiber reinforced PBT system. In bromine-antimony flame-retardant glass fiber reinforced PBT, the bromine-based flame retardant and the PBT matrix have good compatibility. POE-g-GMA with a low grafting rate can achieve the toughening effect. However, this toughening technology cannot be directly applied to glass fiber reinforced halogen-free flame-retardant PBT materials. Existing glass fiber reinforced halogen-free flame-retardant PBT materials have three major performance shortcomings: First, weak interfacial bonding leads to poor toughness. The bond between glass fiber and the PBT matrix is mainly physical, and the halogen-free flame-retardant powder further fills the interface, disrupting the continuity of the phase region. This makes the material extremely sensitive to notches, resulting in low notched impact strength at room temperature and easy brittle fracture at low temperatures, making it unable to withstand assembly impacts and service vibrations. Second, traditional toughening solutions result in significant rigidity loss. The industry generally uses low-grafting-rate POE-g-GMA or ordinary polyolefin elastomers for toughening. Due to the insufficient number of epoxy functional groups, toughening can only be achieved through physical dispersion. Toughening also causes a significant decrease in tensile strength and flexural modulus, making it impossible to achieve both high rigidity and high toughness. Third, flame retardancy and mechanical properties are mutually restrictive. Phosphorus-nitrogen flame retardants have limited flame retardant efficiency, and achieving UL94V-0 rating requires high addition amounts, further exacerbating material embrittlement. Moreover, conventional polyolefin elastomers have poor compatibility with flame retardants, easily leading to appearance defects such as precipitation and fiber floating, affecting the surface quality and long-term reliability of the product.
[0004] Current technologies mainly focus on the toughening and flame retardant optimization of pure PBT systems, without conducting systematic research on the three-phase interface problem of glass fiber filled systems, thus failing to break through the performance bottleneck of glass fiber reinforced halogen-free PBT. Summary of the Invention
[0005] To address the problems in existing technologies, this invention provides a PBT composite material, its preparation method, and its applications. Addressing the interfacial challenges of 30% glass fiber filled systems, this invention selects suitable POE substrates and limits the high grafting rate range of GMA. It relies on the chemical reaction of epoxy functional groups to connect PBT end groups, glass fiber surface hydroxyl groups, and polar groups of flame-retardant powders, constructing a chemically bonded, stable three-phase interfacial structure that achieves a balance between high rigidity, high toughness, and high flame retardancy. Simultaneously, the formulation is simple, requires no special functional additives, is compatible with conventional processing equipment, and has low industrialization costs.
[0006] One of the objectives of this invention is to provide a PBT composite material.
[0007] The composite material is prepared from raw materials including the following components: PBT resin, alkali-free glass fiber, toughening agent, and halogen-free flame retardant; This application directly uses commercial homopolymer PBT resin without the need for pre-chemical modification of PBT; the formulation is simple and does not introduce components such as PET, PC, copolymer PP, basic magnesium sulfate whiskers, thermoplastic polyester elastomers, etc.
[0008] The toughening agent includes ethylene. Octene copolymer grafted with glycidyl methacrylate (POE-g-GMA); The ethylene The glycidyl methacrylate content in the octene copolymer grafted glycidyl methacrylate is 2.5 wt% to 5.0 wt%, preferably 2.5 wt% to 4.0 wt%; for example, 2.5 wt%, 3.0 wt%, 3.5 wt%, 4.0 wt%, 4.5 wt%, and 5.0 wt%.
[0009] GMA grafting rate <2.0%: The number of epoxy functional groups is limited, only achieving limited compatibility, with physical toughening being the main method; the epoxy groups are insufficient to fully react chemically with the PBT terminal carboxyl groups and the hydroxyl groups on the glass fiber surface, and the interface is mainly physically bonded. In the three-phase system where glass fiber and inorganic flame retardant powder coexist, there are many interface defects, limited notched impact enhancement, and significant loss of rigidity while toughening.
[0010] GMA grafting rate 2.5% 5.0%: It has sufficient epoxy functional groups, which can react chemically with PBT terminal carboxyl groups, glass fiber surface hydroxyl groups and flame retardant polar groups during melt processing to form a chemically bonded three-phase interface; it can effectively transfer stress under external force, induce silver creasing, inhibit crack propagation along the interface, and achieve toughening and improvement while almost without losing rigidity, thus achieving a balance between rigidity and toughness.
[0011] GMA grafting rate > 5.0%: The elastomer undergoes significant self-crosslinking, resulting in poor melt flowability and uneven dispersion of elastomer phase domains, causing a decline in the strength and impact performance of the composite material.
[0012] With ethylene Octene copolymer grafted with glycidyl methacrylate as the base material ethylene The octene copolymer, by weight (100%), has an octene unit weight percentage of 18 wt% to 28 wt%, for example, 18 wt%, 19 wt%, 20 wt%, 21 wt%, 22 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, and 28 wt%; ethylene at 190°C and 2.16 kg. Octene copolymer grafted with glycidyl methacrylate as the base material ethylene The melt flow rate of the octene copolymer is 0.5 to 18 g / 10 min, for example 0.5 g / 10 min, 1 g / 10 min, 5 g / 10 min, 10 g / 10 min, 15 g / 10 min, and 18 g / 10 min.
[0013] The octene unit content and melt flow rate of the POE substrate reflect the toughness, modulus, and melt viscosity of the elastomer itself, directly determining the POE content. g The viscosity matching between GMA and the PBT matrix affects the dispersion size and uniformity of elastomer domains within the matrix, further determining the efficiency of interfacial chemical reactions, stress transfer capability, and toughening effect. If the matrix melt index is too low, the elastomer viscosity is too high, making shear dispersion difficult, resulting in coarse domain sizes, a decrease in effective interfacial area, and reduced impact toughness. Conversely, if the matrix melt index is too high, the POE molecular weight is too low, leading to insufficient mechanical strength of the elastomer itself, making it prone to migration and aggregation, disrupting matrix continuity, and causing a significant decrease in the rigidity of the composite material. The octene unit content determines the elasticity and toughening capability of the POE matrix itself. Even with the same GMA grafting rate, mismatched POE matrix parameters will prevent the acquisition of high-performance composite materials; the POE matrix parameters and GMA grafting rate work synergistically.
[0014] Preferably, the components of the composite material are, by weight, 100 parts by weight of PBT resin 30-60 parts by weight of alkali-free glass fiber, preferably 45-60 parts by weight; 3-10 parts by weight of toughening agent, preferably 3-6 parts by weight; 5-20 parts by weight of halogen-free flame retardant, preferably 10-20 parts by weight; Processing aids: 0.3-4 parts by weight; Preferably, the PBT resin is homopolymer polybutylene terephthalate, and its intrinsic viscosity, measured at 25°C using phenol / 1,1,2,2-tetrachloroethane (mass ratio 1:1) as solvent, is 0.8–1.2 dL / g, for example, 0.8 dL / g, 0.9 dL / g, 1.0 dL / g, 1.1 dL / g, or 1.2 dL / g; and the terminal carboxyl group value is ≤30 mol / t, for example, 5 mol / t, 10 mol / t, 15 mol / t, 20 mol / t, 25 mol / t, or 30 mol / t.
[0015] Preferably, the alkali-free glass fiber is a short-cut glass fiber treated with a silane coupling agent, with a single filament diameter of 10-13 μm, such as 10 μm, 11 μm, 12 μm, or 13 μm, and a raw filament length of 3-6 mm, such as 3 mm, 4 mm, 5 mm, or 6 mm; the filling ratio is precisely controlled by side feeding.
[0016] Preferably, the halogen-free flame retardant is composed of aluminum diethylphosphonate (ADP) and melamine polyphosphate (MPP), with the mass ratio of aluminum diethylphosphonate to melamine polyphosphate being (1-5):1; for example, 1:1, 2:1, 3:1, 4:1, 5:1.
[0017] More preferably, the phosphorus content of the aluminum diethylphosphonate is ≥23 wt%; and / or The average particle size of the melamine polyphosphate is ≤15 μm, for example, 1 μm, 3 μm, 5 μm, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm. Phosphorus and nitrogen synergistically improve flame retardant char formation efficiency.
[0018] Preferably, the processing aid includes at least one of antioxidants, lubricants, and nucleating agents; The antioxidant is a combination of hindered phenolic primary antioxidant and phosphite secondary antioxidant in a mass ratio of 1:(1-2); The lubricant is a conventional lubricant in the field of polymer composite materials, preferably pentaerythritol stearate (PETS) or ethylene bis-stearamide (EBS); the dosage is the conventional dosage; The nucleating agent is a conventional nucleating agent in the field of polymer composites, preferably an organophosphonate nucleating agent, such as bis(4) Sodium tert-butylphenyl phosphate, 2,2′ Methylene Double (4,6) Sodium di-tert-butylphenyl) phosphate, bis[2,2′ Methylene Double (4,6) [di-tert-butylphenyl]phosphate aluminum hydroxide; dosage is the standard dosage; used to improve PBT crystallization behavior and enhance product dimensional stability.
[0019] The second objective of this invention is to provide a method for preparing the PBT composite material as described above.
[0020] The preparation method includes: premixing PBT resin, toughening agent, halogen-free flame retardant, and processing aid according to the stated dosage to obtain a premix; adding the premix to an extruder, adding alkali-free glass fiber from the middle side feed port of the extruder, and co-extruding to obtain a composite material.
[0021] The specific steps of the preparation method are as follows: S01: Premix preparation: Add the dried PBT resin, high grafting rate POE-g-GMA, flame retardant and processing aid into a high-speed mixer according to the proportion, mix at room temperature for 1 to 5 minutes to obtain a uniformly dispersed premix. S02: Extrusion granulation: The premixed material is quantitatively added from the main feed port of the twin-screw extruder, and the alkali-free glass fiber is precisely added from the side feed port in the middle section of the extruder; after the material is melt-blended, sheared and conveyed by the screw, it is extruded through the die head, water-cooled and stretched, and air-dried and granulated to obtain composite material particles; S03: Injection Molding Sample Preparation: Dry the composite material particles at 100-120℃ for 4-6 hours, and then injection mold them into standard test strips. Adjust the injection molding process to ensure that the strips are free of bubbles, shrinkage marks, and have a uniform appearance.
[0022] Preferably, the extruder is a twin-screw extruder with a length-to-diameter ratio ≥ 40:1. The temperatures of each section from the feeding section to the die head are sequentially set to 180℃, 225℃, 230℃, 235℃, 235℃, 230℃, 230℃, 230℃, 225℃, and 230℃, with the die head temperature at 235℃. The main motor speed of the twin-screw extruder is 200–500 rpm, for example, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, and 500 rpm, and the vacuum degree is ≥ 0.06 MPa.
[0023] In S03, the injection molding machine barrel temperature is 230-250℃, the mold temperature is 60-90℃, the injection pressure is 60-90MPa, and the holding pressure is 30-50MPa.
[0024] A third objective of this invention is to provide applications of PBT composite materials as described in one objective of this invention or PBT composite materials prepared according to the method described in another objective of this invention in the fields of automotive electronic connectors, low-voltage electrical appliance housings, functional structural components of charging piles, and power tool housings.
[0025] The beneficial effects of this invention are mainly reflected in the following aspects: 1. Three-phase interface synergistic reinforcement achieves toughening without reducing stiffness. High-grafting-rate POE-g-GMA, with its abundant epoxy functional groups, reacts chemically with the PBT terminal carboxyl groups and the silanol groups on the glass fiber surface during melt processing, forming a chemically bonded interfacial transition layer that effectively transfers stress. Compared with low-grafting systems, the notched impact strength is increased by more than 20%, while the tensile strength retention rate is ≥95% and the flexural modulus decreases by <3%, breaking through the industry bottleneck of "toughening inevitably reduces stiffness" in glass fiber reinforced materials.
[0026] 2. Excellent substrate compatibility, with simultaneous improvement in flame retardancy and appearance. The selected POE substrate exhibits excellent compatibility with phosphorus-nitrogen-based halogen-free flame retardants, preventing flame retardant migration and precipitation. During combustion, the elastomer and flame retardant synergistically form char, creating a dense and continuous char layer that blocks heat and oxygen, achieving a stable UL94V-0 rating (1.6mm) even with low flame retardant addition. Simultaneously, improved interface effectively suppresses glass fiber exposure, significantly reducing the fiber floating grade on the product surface and improving appearance quality.
[0027] 3. The formula is simple and versatile, with strong industrial feasibility. This invention does not require the addition of special additives such as phenylsiloxanes and organotin catalysts. Performance breakthroughs can be achieved simply by adjusting the grafting rate of POE-g-GMA and the parameters of the substrate. It is compatible with conventional twin-screw extrusion and injection molding equipment, has a wide processing window, good process stability, and low mass production cost. It can widely replace existing glass fiber reinforced flame-retardant PBT materials. Detailed Implementation
[0028] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.
[0029] It should also be noted that the various specific technical features described in the following embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the various possible combinations will not be described separately in this invention.
[0030] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials and reagents used in the following examples are commercially available or prepared according to conventional methods in the art.
[0031] The present invention will be further described in detail below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.
[0032] (1) Experimental materials PBT resin: Sinopec Yizheng Chemical Fiber, GX121, intrinsic viscosity 1.0 dL / g, terminal carboxyl group value 25 mol / t; Sinopec Yizheng Chemical Fiber, GX112, intrinsic viscosity 0.8 dL / g, terminal carboxyl group value 24 mol / t; Sinopec Yizheng Chemical Fiber, GX122, intrinsic viscosity 1.1 dL / g, terminal carboxyl group value 22 mol / t; Alkali-free chopped glass fiber: Taishan Glass Fiber Co., Ltd., ECS11-3.0-T436H, silane coupling agent treated, monofilament diameter 11μm, filament length 3mm; POE-g-GMA toughening agent: self-made, using POE with different melt indices (0.5 g / 10 min, Dow Chemical, 8150, 25 wt% octene content; 5 g / 10 min, Dow Chemical, 8200, 21% octene content; 18 g / 10 min, Dow Chemical, 8411, 20 wt% octene content; 30 g / 10 min, Dow Chemical, 8407, 28 wt% octene content) as the base material, GMA grafting rate gradient samples were prepared by twin-screw melt grafting, and the grafting rate was tested by acid-base titration method; Comparison of toughening agents: POE / PE-g-GMA (self-made, PE content 5%, GMA grafting rate 1.5%), AX8900 (Arkema, France, EMA-g-GMA), PTW (Dow Chemical, USA, EBA-GMA), CG5001H (Sumitomo, Japan, PE-g-GMA). Halogen-free flame retardants: aluminum diethylphosphinate (ADP), melamine polyphosphate (MPP), industrial grade, Clariant Chemicals (China) Co., Ltd. Processing aids: Antioxidant 1010 (hindered phenolic primary antioxidant) and Antioxidant 168 (phosphite secondary antioxidant), both industrial grade, Tianjin Lianlong New Material Co., Ltd.; Lubricant PETS (pentaerythritol stearate), both industrial grade, Italian FAG.
[0033] The preparation process of POE-g-GMA toughening agent is as follows: (1): Double 2 5-hexyne (2,5) dimethyl 2,5 Bis(tert-butylperoxide) 3 Hexyne and glycidyl methacrylate (GMA) were mixed at a mass ratio of 0.05:1 and mechanically stirred at 400 rpm until double 2 5. Hexyne and GMA were fully fused to obtain an initiator-grafted monomer solution; POE particles (melt index 18 g / 10 min) and antioxidants (1010 and 168, added in a weight ratio of 1:1) (accounting for 6 wt% of the total weight of raw materials (POE, antioxidant, GMA and initiator)) were mechanically stirred at 400 rpm for 5 min to ensure that the antioxidants were fully adhered to the POE particles.
[0034] (2): The POE-antioxidant granules obtained in step (1) were added to the extruder using a loss-in-weight weighing device. The extruder temperature was 160°C. The initiator-graft monomer solution was added in the third zone of the extruder using a liquid pump. The initiator-monomer solution accounted for 3.75 wt% of the total raw material. The extruder pressure was 15 MPa and the speed was 200 rpm. The extruder was cooled and granulated at the die head to obtain ethylene-octene copolymer grafted glycidyl methacrylate with a grafting rate of 2.5% (grafting rate = GMA weight / POE weight * 100%).
[0035] With everything else remaining the same, the amounts of initiator-grafting monomer solution used in step (2) above were changed to 0.75%, 4.5%, 5.25%, 6%, 6.75%, and 7.5%, respectively, to obtain ethylene-octene copolymer grafted with glycidyl methacrylate with grafting rates of 0.5%, 3.0%, 3.5%, 4.0%, 4.5%, and 5.0%.
[0036] Keeping everything else unchanged, by changing the melt index of the POE particles in step (1) above, ethylene-octene copolymer grafted glycidyl methacrylate with different melt indices can be obtained.
[0037] Comparing the toughening agent: The preparation process of POE / PE-g-GMA (PE content 5%, GMA grafting rate 1.5%) is as follows: everything else remains the same, except in step (1), POE particles and PE particles (based on the total weight of raw materials of 100%, PE content of 5wt%) are mixed with antioxidant. In step (2), the amount of initiator-grafting monomer solution is 2.25%, and POE / PE-g-GMA with a grafting rate of 1.5% is obtained.
[0038] (2) Preparation process S01: Dry PBT resin in a 120℃ forced-air drying oven for 4 hours. Weigh PBT, toughening agent, halogen-free flame retardant and processing aid according to the formula ratio, add them to a high-speed mixer, mix at room temperature for 3 minutes to obtain a uniform premix. S02: The premixed material is added to the main feed hopper of the twin-screw extruder, and the glass fiber is added quantitatively from the side feed port of zone 6; the temperature of each section of the extruder is 220-250℃, the screw speed is 350rpm, the vacuum degree is 0.07MPa, and after melt blending, it is extruded into strips through the die, water-cooled, air-dried, and pelletized to obtain composite material particles. S03: Dry the composite material particles at 110℃ for 5 hours, and prepare standard test specimens using an injection molding machine with an injection temperature of 240℃, a mold temperature of 80℃, and an injection pressure of 75MPa.
[0039] (3) Performance testing standards Tensile strength and elongation at break: tested according to GB / T1040.2-2006, tensile rate 5 mm / min; Bending strength and bending modulus: tested according to GB / T9341-2008, span 64mm, test rate 2mm / min; Notched impact strength of simply supported beams: tested according to GB / T1043.1-2008, type A notch, test temperature 23℃; Unnotched impact strength: Tested according to GB / T1043.1-2008, test temperature 23℃; Vertical burning performance: tested according to UL94-2013 standard, with a sample thickness of 1.6 mm.
[0040] 4) Examples and Comparative Formulations This experiment was divided into two groups: the first group investigated the effect of GMA grafting rate on material properties; the second group investigated the melt index of POE substrate and the performance differences of different commercially available toughening agents. All groups had fixed amounts of PBT 100 parts by weight, glass fiber 52 parts by weight, toughening agent 5 parts by weight, ADP 10 parts by weight, MPP 5 parts by weight, antioxidant 1010 0.3 parts by weight, antioxidant 168 0.3 parts by weight, and lubricant PETS 0.5 parts by weight.
[0041] Example 1 100 parts of PBT resin, 5 parts of toughening agent POE-g-GMA (grafting rate 2.5%), 10 parts of aluminum diethylphosphonate (ADP), 5 parts of melamine polyphosphate (MPP), 0.3 parts of antioxidant 1010, 0.3 parts of antioxidant 168, and 0.5 parts of lubricant PETs were mixed according to step S01 and then proceeded to step S02 to obtain a 30% glass fiber halogen-free flame-retardant reinforced PBT composite material.
[0042] Example 2 The preparation process is the same as in Example 1, except that POE-g-GMA (grafting rate 2.5%) is replaced with POE-g-GMA (grafting rate 3.0%).
[0043] Example 3 The preparation process is the same as in Example 1, except that POE-g-GMA (grafting rate 2.5%) is replaced with POE-g-GMA (grafting rate 3.5%).
[0044] Example 4 The preparation process is the same as in Example 1, except that POE-g-GMA (grafting rate 2.5%) is replaced with POE-g-GMA (grafting rate 4.0%).
[0045] Example 5 The preparation process is the same as in Example 1, except that POE-g-GMA (grafting rate 2.5%) is replaced with POE-g-GMA (grafting rate 4.5%).
[0046] Example 6 The preparation process is the same as in Example 1, except that POE-g-GMA (grafting rate 2.5%) is replaced with POE-g-GMA (grafting rate 5.0%).
[0047] Example 7 The preparation process is the same as in Example 3, except that the POE substrate of 18 g / 10 min in POE-g-GMA (grafting rate 3.5%) is replaced with POE substrate with a melt index of 0.5 g / 10 min.
[0048] Example 8 The preparation process is the same as in Example 3, except that the POE substrate in POE-g-GMA (grafting rate 3.5%) is replaced with a POE substrate with a melt index of 5g / 10min.
[0049] Example 9 The preparation process is the same as in Example 8, except that the ratio of aluminum diethylphosphonate (ADP) to melamine phosphate (MPP) is adjusted from 2:1 to 4:1 (the total amount of flame retardant remains unchanged).
[0050] Example 10 The preparation process is the same as in Example 8, except that PBT (viscosity 1.0 dL / g) is replaced with PBT (viscosity 0.8 dL / g). Example 11 The preparation process is the same as in Example 8, except that PBT (viscosity 1.0 dL / g) is replaced with PBT (viscosity 1.1 dL / g). Comparative Example 1 The preparation process is the same as in Example 1, except that POE-g-GMA (grafting rate 2.5%) is replaced with POE-g-GMA (grafting rate 0.5%).
[0051] Comparative Example 2 The preparation process is the same as in Example 1, except that POE-g-GMA (grafting rate 2.5%) is replaced with POE / PE-g-GMA (grafting rate 1.5%).
[0052] Comparative Example 3 The preparation process is the same as in Example 1, except that POE-g-GMA (grafting rate 2.5%) is replaced with AX8900.
[0053] Comparative Example 4 The preparation process is the same as in Example 1, except that POE-g-GMA (grafting rate 2.5%) is replaced with PTW.
[0054] Comparative Example 5 The preparation process is the same as in Example 1, except that POE-g-GMA (grafting rate 2.5%) is replaced with CG5001H.
[0055] Comparative Example 6 The preparation process is the same as in Example 3, except that the POE substrate with a POE content of 18 g / 10 min in POE-g-GMA (grafting rate 3.5%) is replaced with a POE substrate with a melt index of 30 g / 10 min.
[0056] The specific formulation ratios for the examples and comparative examples are shown in the table below. Table 1. Formulations of Examples
[0057] Table 2. Comparative Formulas
[0058] The table below shows the performance test results of the examples and comparative examples. Table 3. Test Performance Results
[0059] Based on the performance test data from all embodiments and comparative examples, it can be seen that the GMA grafting rate is the core parameter for controlling the three-phase interface bonding and balancing rigidity and toughness of 30% glass fiber reinforced halogen-free flame-retardant PBT. As the GMA grafting rate increases from 0.5% to 3.0%, the notched impact strength of the composite material increases from 6.91 kJ / m² to 8.40 kJ / m², an increase of 21.6%, while the unnotched impact strength increases simultaneously from 42.67 kJ / m² to 50.26 kJ / m². This is because the increased grafting rate increases the number of epoxy functional groups on the elastomer surface, which can fully react with the PBT terminal carboxyl groups and the hydroxyl groups on the glass fiber surface during melt processing, forming a chemically bonded interface layer. Under external force, the elastomer can effectively induce creasing, absorb impact energy, and simultaneously inhibit crack propagation along the glass fiber interface. Furthermore, as the grafting rate increases from 0.5% to 3.5%, the composite material's impact strength also increases. During the process, the tensile strength of the material increased from 120MPa to 124MPa, and the flexural modulus remained above 10300MPa. However, when the grafting rate exceeded 4.0%, the tensile and flexural strengths slightly decreased. This is because an excessively high grafting rate can easily lead to cross-linking of the elastomer itself, resulting in decreased melt flowability and poor dispersion uniformity, which in turn causes a decline in mechanical properties. Moreover, all groups consistently passed the UL94V-0 level (1.6mm), indicating that the phosphorus-nitrogen compound flame retardant scheme of this system is highly efficient and reliable. High-grafted POE-g-GMA can help promote char formation and has a positive effect on flame retardant performance. There was no problem of elastomer dilution of flame retardant effect. In summary, a GMA grafting rate ≥2.5% in this system can achieve significant toughening and efficiency enhancement, and the optimal grafting rate range is 3.0% to 4.0%, at which point the material's rigidity and toughness reach the best balance.Under the condition of a fixed GMA grafting rate of 3.5%, the melt flow rate of the POE substrate directly affects the dispersion state and interfacial bonding effect of the elastomer in the matrix. When the melt flow rate of the substrate is 5 g / 10 min, the overall material performance is optimal, with tensile strength reaching 121 MPa, flexural modulus reaching 10553 MPa, notched impact strength reaching 8.19 kJ / m², and unnotched impact strength reaching 53.86 kJ / m². At this point, the elastomer melt viscosity matches the PBT matrix best, forming uniformly sized dispersed phase domains, with sufficient interfacial bonding, and maximizing both toughening and strengthening efficiency. When the melt flow rate of the substrate is 0.5 g / 10 min, the elastomer viscosity is too high, and the dispersed particle size in the melt blend is too large. As the interfacial area decreases, both impact and tensile properties decline slightly. When the melt flow index (MFI) rises to 30 g / 10 min, the material's mechanical properties deteriorate significantly, with tensile strength dropping to 92.6 MPa and flexural modulus to 9513 MPa. This is because high MFI POE has a low molecular weight, resulting in insufficient strength. Furthermore, it is prone to migration and aggregation during processing, failing to effectively transfer stress and disrupting matrix continuity, leading to a significant decrease in rigidity. Therefore, the optimal MFI range for POE substrates adapted to 30% glass fiber halogen-free flame-retardant PBT systems is 0.5–18 g / 10 min, preferably around 5 g / 10 min. Once the MFI exceeds 30 g / 10 min, the material's overall performance cannot meet the requirements for structural components. Comparison with different types of commercially available toughening agents reveals that while the introduction of the PE component improves the crystallinity of the elastomer in POE / PE-g-GMA, it reduces its compatibility with PBT, resulting in an unnotched impact strength of only 44.06 kJ / m², far lower than the toughening effect of ethylene-octene pure POE substrate. Although ternary copolymer toughening agents such as AX8900 and PTW possess high GMA grafting rates, the low modulus and poor rigidity of the substrate itself lead to a decrease in the tensile strength of the composite material to 108 MPa and 113 MPa, respectively, and the flexural modulus is also lower than that of the present invention. The proposed solution cannot meet the requirements for high-rigidity structural components; E-GMA copolymers such as CG5001H lack elastic monomers and rely solely on the reaction of high-content epoxy groups with PBT, which significantly reduces the flexural strength of the material to 108.5 MPa, only 55.9% of the optimal value of this invention, resulting in severe rigidity loss and making it unsuitable for glass fiber reinforced systems. This verifies that the ethylene-octene POE substrate combined with highly grafted GMA selected in this invention is significantly superior to mainstream toughening agents on the market in terms of rigidity retention, toughening efficiency, and flame retardant compatibility, demonstrating clear performance advantages.In summary, this invention clarifies the grafting rate threshold and optimal range of POE-g-GMA in a 30% glass fiber reinforced halogen-free flame-retardant PBT system. When the GMA grafting mass fraction is ≥2.5%, the glass fiber-PBT-flame retardant three-phase interface can be significantly strengthened through chemical bonding, achieving an increase in notched impact strength of over 20%. At a grafting rate of 3.0%–4.0%, the material achieves the best balance between rigidity and toughness. Simultaneously, suitable POE substrate parameters for this system were screened. The ethylene-1-octene copolymer substrate exhibits excellent comprehensive performance within the melt flow rate range of 0.5–18 g / 10 min, with the melt flow rate at 5 g / 10 min being particularly high. With optimal dispersion and interface integration, the optimal formulation of this invention achieves a tensile strength of 124 MPa, a flexural modulus of 10404 MPa, and a notched impact strength of 8.40 kJ / m² for a simply supported beam. Simultaneously, it stably passes the UL94V-0 flame retardant rating at a thickness of 1.6 mm. Its performance balance is significantly superior to existing low-grafted POE-g-GMA and commercially available acrylate toughening agent solutions. Furthermore, the formulation is simple, requiring no special functional additives, and is compatible with conventional twin-screw extrusion and injection molding processes. It offers a wide processing window, low mass production costs, and can be widely applied in high-end fields such as automotive electronics, low-voltage electrical appliances, and new energy charging piles, demonstrating significant industrialization potential.
[0060] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.
Claims
1. A PBT composite material, characterized in that, The composite material is prepared from raw materials including the following components: PBT resin, alkali-free glass fiber, toughening agent, and halogen-free flame retardant; The toughening agent includes ethylene. Octene copolymer grafted with glycidyl methacrylate; The ethylene The glycidyl methacrylate content in the octene copolymer grafted glycidyl methacrylate is 2.5 wt% to 5.0 wt%, preferably 2.5 wt% to 4.0 wt%. With ethylene Octene copolymer grafted with glycidyl methacrylate as the base material ethylene The octene copolymer, by weight (100%), has an octene unit weight percentage of 18 wt%–28 wt%; ethylene at 190℃ and 2.16 kg. Octene copolymer grafted with glycidyl methacrylate as the base material ethylene The melt flow rate of the octene copolymer is 0.5–18 g / 10 min.
2. The PBT composite material according to claim 1, characterized in that, The components of the composite material are described in parts by weight. 100 parts by weight of PBT resin 30-60 parts by weight of alkali-free glass fiber, preferably 45-60 parts by weight; 3-10 parts by weight of toughening agent, preferably 3-6 parts by weight; 5 to 20 parts by weight of halogen-free flame retardant, preferably 10 to 20 parts by weight.
3. The PBT composite material according to claim 1, characterized in that, The PBT resin is homopolymer polybutylene terephthalate, with an intrinsic viscosity of 0.8–1.2 dL / g at 25°C and a terminal carboxyl group value ≤30 mol / t.
4. The PBT composite material according to claim 1, characterized in that, The alkali-free glass fiber is a short-cut glass fiber treated with a silane coupling agent, with a single filament diameter of 10-13 μm and a filament length of 3-6 mm.
5. The PBT composite material according to claim 1, characterized in that, The halogen-free flame retardant is composed of aluminum diethylphosphonate and melamine polyphosphate, with a mass ratio of aluminum diethylphosphonate to melamine polyphosphate of (1-5):
1. Preferably, the phosphorus content of the aluminum diethylphosphonate is ≥23 wt%; and / or The average particle size of the melamine polyphosphate is ≤15μm.
6. The PBT composite material according to claim 1, characterized in that, The processing aids include at least one of antioxidants, lubricants, and nucleating agents; Preferably, the antioxidant is a combination of hindered phenolic primary antioxidant and phosphite secondary antioxidant in a mass ratio of 1:(1-2); The lubricant is pentaerythritol stearate or ethylene bis-stearamide; The nucleating agent is an organophosphonate nucleating agent.
7. A method for preparing a PBT composite material as described in any one of claims 1-6, characterized in that, The preparation method includes: premixing PBT resin, toughening agent, halogen-free flame retardant, and processing aid according to the stated dosage to obtain a premix; adding the premix to an extruder, adding alkali-free glass fiber from the middle side feed port of the extruder, and co-extruding to obtain a composite material.
8. The method for preparing the PBT composite material according to claim 7, characterized in that, The extruder is a twin-screw extruder with a length-to-diameter ratio ≥ 40:
1.
9. The method for preparing the PBT composite material according to claim 8, characterized in that, The twin-screw extruder has a main engine speed of 200-500 rpm and a vacuum degree of ≥0.06 MPa.
10. The application of the PBT composite material as described in any one of claims 1-6 or the PBT composite material prepared according to the method described in any one of claims 7-9 in the fields of automotive electronic connectors, low-voltage electrical appliance housings, charging pile functional structural components, and power tool housings.
